A multigeneration system of combined cooling, heating, and power (CCHP) for low-temperature geothermal system by using air cooling. (1st March 2021) - Chaiyat, Nattaporn
Highlights: To present a novelty model of the energy, exergy, economic and environment impacts. Combined cooling (absorption chiller) heating (drying room) and power (organic Rankine cycle) is implemented. A cascade utilization of air-cooled multigeneration system of San Kamphaeng hot spring, Thailand. To evaluate thermal performance of the air-cooled multigeneration system. Abstract: A new definition of the energy, exergy, economic and environmental model (3, 4E-Chaiyat models) was used to evaluate cascade air-cooled multigeneration from a single-stage organic Rankine cycle of 10 kWe, a single-stage absorption chiller of 15 kW, and a drying room of 20 kW, respectively. From the study results, a first-law efficiency of 17.23% was found to be higher than a second-law efficiency of 15.13%. According to a life cycle assessment (LCA), a single score of the energy model of approximately 0.0250Pt was lower than that of the exergy model of approximately 0.1223Pt. In the 3E model, a levelized energy cost per life cycle assessment (LEnCA) was approximately 0.0017 USD⋅Pt/kWh 2 for an investment cost of 159, 729 USD. At the same time, in the 4E model, a levelized exergy cost per life cycle assessment (LExCA) was approximately 0.0414 USD⋅Pt/kWh 2, which was lower than that of the water-cooled multigeneration system (approximately 0.0442 USD⋅Pt/kWh 2 ). Thus, the suitable cooling type for the cascade geothermal-multigeneration system used in San Kamphaeng, Thailand, is the air-cooled type.